Digital Forensic Ethical Data Handling in Indonesia - Thealma, Feby; Rudelviani, Yova (The Indonesian Journal of Computer Science, 2025)
Digital evidence in digital forensic investigations may contain sensitive information which includes private data, however none of the digital forensic standards used in Indonesia focuses on the ethical data handling aspect. Concerning the recent release of Indonesia’s Private Data Protection law, this research aims to find clauses in the law that has not been addressed in the digital forensic standards. This research is conducted by correlating Indonesia’s Private Data Protection law against digital forensic standards used in Indonesia to find how Indonesia’s Private Data Protection law has been complied with the usage of digital forensic standards. As of now, only half of the existing digital forensic standards used in Indonesia has explicitly complied with Indonesia’s Private Data Protection law and there are room for improvement to enhance digital forensic ethical data handling in Indonesia.